2019
DOI: 10.3389/fmicb.2019.02736
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Heterogeneity and Connectivity: Effects on the Planktonic Protist Community Structure at Two Adjacent Coastal Sites (the Lagoon and the Gulf of Venice, Northern Adriatic Sea, Italy) Revealed by Metabarcoding

Abstract: The Lagoon of Venice (LoV) and the Gulf of Venice (GoV), two adjacent coastal Long Term Ecological Research (LTER) sites in the northern Adriatic Sea, represent a transitional/marine coupled ecosystem under the influence of regional and local factors. In this study, these sites were sampled on four dates from April 2016 to February 2017 for environmental DNA and relevant abiotic variables, aiming to assess the relative importance of habitat heterogeneity and connectivity in structuring the protist community. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 100 publications
4
21
0
Order By: Relevance
“…Nanoflagellates are difficult or impossible to identify with light microscopy and in routine phytoplankton long-term monitoring they will very likely always be left undetermined, so that an important part of the phytoplankton biodiversity will remain hidden. Actually, recent studies on the VL protists through metabarcoding [59,60] revealed that nanoflagellates are represented by several distinct species, some of which (e.g., Picochlorum, Micromonas) were reported for the first the lagoon in that study.…”
Section: Discussionmentioning
confidence: 90%
“…Nanoflagellates are difficult or impossible to identify with light microscopy and in routine phytoplankton long-term monitoring they will very likely always be left undetermined, so that an important part of the phytoplankton biodiversity will remain hidden. Actually, recent studies on the VL protists through metabarcoding [59,60] revealed that nanoflagellates are represented by several distinct species, some of which (e.g., Picochlorum, Micromonas) were reported for the first the lagoon in that study.…”
Section: Discussionmentioning
confidence: 90%
“…autotrophy, mixotrophy, heterotrophy) because of its importance for phytoplankton fitness. While with microscopy each taxon can be assigned to a trophic role based on genus or species identification, with HTS this assignation is based on phylum or family level (Machado et al, 2019; Minicante et al, 2019). Furthermore in biodiversity assessments, the % contribution of phyla to the total community is often compared between microscopy and HTS (Eiler et al, 2013; Giner et al, 2016; Piredda et al, 2017; Wright et al, 2019; Xiao et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Surprisingly, higher phytoplankton diversity indices were observed during spring and fall, seasons where phytoplankton blooms are likely to occur in Mediterranean coastal ecosystems (Ribera d'AlcalĂ  et al, 2004); algal blooms often being concomitant with low phytoplankton diversity (Lehtinen et al, 2017;Livingston, 2007). Phytoplankton diversity was significantly higher (p < 0.05) in offshore waters -16-relative to lagoon waters, contrasting that observed in other lagoons where phytoplankton diversity in the enclosed system can be higher (Srichandan et al, 2019) or equivalent (Minicante et al, 2019) to their adjacent waters. These contrasting results…”
Section: In Situ Phytoplankton and Bacterioplankton Diversitymentioning
confidence: 85%